Test Application for Growth Promoting Rhizobacteria (PGPR) and Planting Media to Grow the Growth and Yield of Shallot Plants (Allium ascalonicum L.) Varieties of Bauji - Rahadianto, Prabowo; Maftuchah; Ikhwan, Ali (Universitas Muhammadiyah Malang, 2024)
The main commodity of food crops is rice which has a strategic function, namely as a staple food for the people of Indonesia. Maintaining the health and quality of soil biologically by reducing dependence on synthetic fertilizers. Swamp Inbred Paddy (Inpara) are superior varieties of paddy that are well cultivated in swamp land conditions, resistant to immersion, and adaptability to acidic soil conditions. This study investigates the combination of biological and synthetic fertilizers on the growth of flood-tolerant Inpara rice using a strip plot/split block design. The treatments used were 6 combinations of biological fertilizers-synthetic fertilizers and 3 paddy varieties with 3 replications. The results obtained from the analysis of variance then conducted a further test of BNJ to determine the performance of each variable. Correlation test is performed to determine the interactions and relationships between observational variables. Soil analysis is also carried out to determine the mineral content in the soil. The effect of the combination of synthetic and biological fertilizer doses with 3 Inpara paddy varieties interacted significantly on several observational variables resulting in significantly different performance. The combination treatment with 75% synthetic fertilizer and 25% biological fertilizer showed several parameters that were higher than the treatment with 100% synthetic fertilizer so that the use of synthetic fertilizer can be reduced.